1998
DOI: 10.3109/00048679809073879
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Professionals' Attire

Abstract: Psychiatrists and case managers in a community mental health team could consider adopting less formal attire. This conclusion is limited by the small sample and may be relevant to rural areas only. Further research is needed in urban centres. Implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Rajagopalan and colleagues found some support for this claim in their observation that while most patients with mental health concerns did not feel that the dress of psychiatrists and case workers was an important issue, those who did preferred less formal attire. 17 Similarly, a recent study reported no differences in overall patient satisfaction among obstetricians randomly assigned to dress in business attire, casual clothing, or scrubs. 18 Disparity among physician groups may be due to specialty-specific differences in the demographics of the patient populations and in patient-physician relationships.…”
Section: Introductionmentioning
confidence: 95%
“…Rajagopalan and colleagues found some support for this claim in their observation that while most patients with mental health concerns did not feel that the dress of psychiatrists and case workers was an important issue, those who did preferred less formal attire. 17 Similarly, a recent study reported no differences in overall patient satisfaction among obstetricians randomly assigned to dress in business attire, casual clothing, or scrubs. 18 Disparity among physician groups may be due to specialty-specific differences in the demographics of the patient populations and in patient-physician relationships.…”
Section: Introductionmentioning
confidence: 95%
“…It has also been suggested that patient preference may be linked to physician specialty. For example, patients appear to be more accepting of casually dressed psychiatrists11, and emergency room physicians 12. In a recent study assessing patient satisfaction with care among obstetricians in an outpatient setting satisfaction was not found to be influenced by attire 13.…”
Section: Introductionmentioning
confidence: 99%
“…The recent article on mental health professionals' attire [1] confirms my clinical impression that patients either don't care what their psychiatrists wear or prefer a more casual look. I have struggled with this issue since my medical student days, when my friends and I would carry our short white coats over our shoulders on hot days, rather than swelter.…”
mentioning
confidence: 88%